Beyond the Bedroom: How Resilience and Thought Control Influence Sexual Satisfaction - Rostami, Mehdi (KMAN Counseling & Psychology Nexus, 2023)
This study aimed to explore the predictive relationships between resilience, thought control, and sexual satisfaction among adults in romantic relationships. Utilizing a cross-sectional design, data were collected from 450 participants through validated scales measuring sexual satisfaction (Index of Sexual Satisfaction), resilience (Connor-Davidson Resilience Scale), and thought control (Thought Control Questionnaire). Multiple linear regression analysis was conducted using SPSS-27 to examine the predictive value of resilience and thought control on sexual satisfaction. The regression analysis revealed that both resilience (β = 0.29, p < 0.01) and thought control (β = 0.30, p < 0.01) significantly predicted sexual satisfaction, accounting for 49% of the variance in sexual satisfaction scores. The findings suggest a substantial relationship between these psychological constructs and sexual satisfaction. The study underscores the importance of resilience and thought control as significant predictors of sexual satisfaction. These findings highlight the need for incorporating psychological resilience and cognitive strategies into interventions aimed at enhancing sexual well-being in intimate relationships.